Characterization, biological activities, and authentication of red fruit (Pandanus conoideus Lam) oil - Rohman, A.; Windarsih, A. (Food Research, 2017)
Red fruit (Pandanus conoideus Lam) oil (RFO) is one of high value edible oils having many functional advantages for health. P. conoideus is a native plant from Papua province, Republic of Indonesia and Papua New Guinea. RFO is good for diets and served as preventive agents for various diseases such as cancer and coronary disease so that RFO can be considered as functional edible oils. Because of its high quality, in Indonesia fats and oils market, RFO has a more expensive price (10-15 times) than other common edible oils like palm oil and corn oil. This fact attracts some unethical player to adulterate RFO with other lower priced-oils such as palm oil and corn oil. As a consequence, the authentication of RFO from any oil adulterants becomes important to ensure the quality and the authenticity of RFO. This article report some biological advantages of RFO and the characterization of RFO. FTIR spectroscopy in combination with multivariate calibrations has been reported as a powerful technique for the authentication of RFO from other oils and is the most reported techniques in some literature.